Association of educational attainment with esophageal cancer, Barrett's esophagus, and gastroesophageal reflux disease, and the mediating role of modifiable risk factors: A Mendelian randomization study - Zhang, Xuening; Yang, Xiaorong; Zhang, Tongchao; Yin, Xiaolin; Man, Jinyu; Lu, Ming (Frontiers in Public Health, 2023)
Background: Observational studies have reported that educational attainment has been related to the risk of esophageal cancer (EC) and its precancerous lesions. However, the causal relationship remains controversial. We aimed to apply the Mendelian randomization (MR) design to determine the causal associations between genetically predicted educational attainment and EC, Barrett´s esophagus (BE), and gastroesophageal reflux disease (GERD), and to explore whether modifiable risk factors play mediating role. Methods: Using summary statistics from genome-wide association studies (GWAS) based on European ancestry individuals of number of years in education (EduYears, primary analysis, n = 293,723), college completion (College, secondary analysis, n = 95,427), EC (n = 420,531), BE (n = 361,194), and GERD (n = 420,531), genetic associations between two education phenotypes and EC, BE, and GERD were tested by two-sample MR analyses. Then, two-step MR mediation analyses were used to assess the proportion of the above association that might be mediated by body mass index (BMI), major depressive disorder (MDD), smoking, drinking, carbohydrates, fat, and protein intake. Results: Genetically predicted EduYears was negatively associated with the risk of EC, BE, and GERD (odds ratio, 0.64 [95% confidence interval (CI) 0.44-0.94], 0.83 [95% CI, 0.73-0.96], and 0.62 [95%CI, 0.58-0.67]). EduYears was negatively associated with BMI, MDD, and smoking (OR ranged: 0.76-0.84). There were positive associations between BMI, smoking with EC, BE, and GERD, as well as between MDD with GERD (OR ranged: 1.05-1.50). For individual mediating effect, BMI and smoking mediated 15.8% and 15.9% of the EduYears-EC association, and 12.7% and 13.2% of the EduYears-BE association. BMI, MDD, and smoking mediated 5.2%, 5.0%, and 4.5% of the EduYears-GERD association. For combined mediation, the above mediators explained 27.6%, 21.8%, and 11.5% of the effect of EduYears on EC, BE, and GERD. The mediating effects of drinking and dietary composition were not significant in the effect of education on EC, BE, and GERD. Conclusions: Our study supports that genetically predicted higher educational attainment has a protective effect on EC, BE, and GERD, and partly mediated by reducing adiposity, smoking, and depression.